Tinjauan dan Analisis Tren Penelitian Berpikir Komputasi dalam Pendidikan Matematika (2013-2023) - Fitriyah, Yuni; Dahlan, Jarnawi Afgani; Maghfiroh, Fitria; Wahyudin, Wahyudin (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
This research aims to examine the development of computational thinking research publications in mathematics education (ME) from 2013 to 2023 and explore information networks based on keywords and author collaborations. The methodology used in this research is descriptive bibliometric analysis. Data collection was carried out using the Scopus database with the keywords 'computational thinking' and 'mathematics education'. Data was collected via the Publish or Perish application, 99 publications were obtained for analysis using VOSviewer. Bibliometric mapping results reveal that CT in ME remains a continuously observed and evolving topic, with significant increases over the past 11 years. The most dominant country in this field of research is the United States. Bibliometric mapping identified collaborations between authors from various countries, with Chee-Kit Looi recognized as the most influential contributor. Mapping based on the occurrence of keywords identifies relationships between scientific concepts, forming several dominant groups. Keywords that appear limited include CT in teacher aspects through teaching practices, learning approaches, and assessment. Research on this topic is relatively scarce with respect to STEM education, providing opportunities for future research and broader development in this area.